Fusarium mycotoxins and in vitro species-specific approach with porcine intestinal and brain in vitro barriers: A review. (November 2018) - Bertero, A.; Spicer, L.J.; Caloni, F.
Abstract: Fusarium mycotoxins, such as fumonisins, trichothecenes, zearalenone and emerging fusariotoxins, common contaminants of feed and food, have received increased interest, due to the possible impact on animal and human health. In this context, it is urgent to focus our attention on fusariotoxins adverse effects, considering and analysing data in relation to their species-specificity. The in vitro approach for fusariotoxins risk assessment evaluation, through porcine epithelial barriers model, allowed to collect information on their absorption profile, bioavailability and toxicity. The aim of this review is to give an overview on Fusarium mycotoxins and their interactions with porcine intestinal and brain in vitro barriers, because they represent direct target organs of toxicity and as tools to evaluate their permeability and transport. Highlights: Fusarium effects mycotoxins on barrier and other functions of porcine intestinal epithelial cell lines (IPEC) are reviewed. Effects of Fusarium mycotoxins on function of primary porcine brain capillary endothelial cells (PBCEC) are reviewed. Specific effects of zearalenone, fumonisin B1, deoxynivalenol, T2 toxin, beauvericin, enniatins on IPEC are compared. Specific effects of T2 toxins, enniatins, and moniliformin on PBCEC are compared. Effects of zearalenone, fumonisin B1, beauvericin, enniatins, and T2 toxin, on IPEC and PBCEC are compared.